Optimalisasi Media Sosial sebagai Media Penggerak Komunitas Masyarakat dalam Mengelola Sampah Rumah Tangga di Desa Sumberkejayan, Mayang, Jember - Nurul Laili Fadhilah; Pratiwi Puspitho Andini; Bayu Dwi Anggono; Tutik Patmiati; Muhlisin Muhlisin; Puspa Maharani; Intan Nuraini (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2025)
Social media has become a massive medium for socialization, education, and learning, including education on minimizing waste. Moreover, almost everyone has social media nowadays, so it is not only a necessity but also a lifestyle. This includes the lifestyle of turning waste into something more meaningful and useful, one of which is by managing organic waste into eco enzymes. Eco enzymes produced from household waste management are managed by educating the community to be more prudent in managing the waste they produce. Social media is capable of providing ideas for education and socialization in various fields. The participants in this empowerment program are mostly productive-aged individuals who are familiar with social media, making this empowerment easy to understand. This empowerment is supported by several community accounts and personal accounts whose content focuses on managing organic waste and networking with other communities. Community development through this social movement can provide motivation and support for zero waste programs and movements as an effort to minimize waste for the sustainability of the environment. Because waste is not only our responsibility but a shared responsibility. Support for this program will certainly have a greater impact if it involves the younger generation.